2020
DOI: 10.1177/0954411920950904
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the optimum puncture pattern of robot-assisted needle insertion into hyperelastic materials

Abstract: The robot-assisted insertion surgery plays a crucial role in biopsy and therapy. This study focuses on determining the optimum puncture pattern for robot-assisted insertion, aiming at the matching problem of needle insertion parameters, thereby to reduce the pain for patients and to improve the reachability to the lesion point. First, a 6-degrees of freedom (DOFs) Computed Tomography (CT)-guided surgical robotic system for minimally invasive percutaneous lung is developed and used to perform puncture experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…13 The stiffness and cutting forces will be unaffected by the vibration, therefore only the friction force is influenced by the bioinspired needle design and the vibration. 7,42,[44][45][46][47][48] For example, Wu et al 48 have observed that vibration can decrease the friction force, but it does not influence the effect of tissue stiffness on the needle body. Our results show that this is true up to 200 Hz frequency but at higher frequencies and above 30 mm insertion depth, it shows a reverse trend.…”
Section: Discussionmentioning
confidence: 99%
“…13 The stiffness and cutting forces will be unaffected by the vibration, therefore only the friction force is influenced by the bioinspired needle design and the vibration. 7,42,[44][45][46][47][48] For example, Wu et al 48 have observed that vibration can decrease the friction force, but it does not influence the effect of tissue stiffness on the needle body. Our results show that this is true up to 200 Hz frequency but at higher frequencies and above 30 mm insertion depth, it shows a reverse trend.…”
Section: Discussionmentioning
confidence: 99%
“…Rotational movement can reduce tissue displacement and friction before puncture. Since biological tissues are generally non-uniform and anisotropic, their mechanical properties depend on position and direction respectively [158,159]. Therefore, the position and direction of the insertion are particularly important.…”
Section: Needle-tissue Interactionmentioning
confidence: 99%